Lecturers’ Perceptions of the Use of E-Learning in Supporting Performance in the English Language Education Study Program - Nuraini, Hery; Sholeh Hidayat; Lukman Nulhakim (EDUTEC : Journal of Education And Technology, 2024)
This research aims to explore lecturers’ perceptions of the use of e-learning in supporting performance in the English Language Education Study Program. Data was collected through a survey using a questionnaire distributed to lecturers at several universities. The research results show that the majority of lecturers have good knowledge about e-learning and recognize its benefits in supporting the learning process. However, problems related to accessibility and quality of internet networks are a major concern, with most lecturers stating that e-learning is ineffective for students in areas with limited internet access. Despite facing technical challenges, the majority of lecturers still feel happy and satisfied in using e-learning as a learning medium. In conclusion, efforts to improve technological infrastructure, training and support related to e-learning must be strengthened to improve the quality of learning and performance of lecturers in the English Language Education Study Program.